Student’s Perception toward Learning Management System in Studying Organic Chemistry During Pandemic Covid-19 - Khalidi Omar, Muhammad Haiqal Amir; Faroerzy, Nik Nurul Izzah; Nordin, Norbaizura (Multidisciplinary Applied Research and Innovation, 2023)
During the Coronavirus pandemic (Covid-19), this lethal disease touched many sectors of life, including schooling. In most nations, educational institutions have been shuttered and e-learning has been required. Higher Education Institutions (HEIs) were not always equipped to give their whole curricula online. As a result, in order to reposition themselves, several HEIs have turned to Learning Management System (LMS) to help them develop and survive. LMS is software used for delivering, tracking and managing training or education. Therefore, the first objective of this study is to identify the most difficult chemistry courses in Diploma in Engineering Technology (DAK) program.Then, to identify the best learning and teching method. In addition, this study is to develop the LMS platform in studying Organic Chemistry. This study is mainly focusing on DAK students. The ADDIE concept served as a model for the development of LMS. A Likert-scale questionnaire was part of the study’s quantitative research approach. Data was collected and analyzed using Statistical Package for the Social Science (SPSS) and descriptive analysis. The results showed that Organic Chemistry, with a mean score of 3.92, had the highest mean of the easiest and hardest subjects that offered in the DAK course during year 1. For the student’s perception of using the LMS, the lowest mean of users’ perceived students’ comprehension is 1.23 for the question "Are the notes offered in this LMS easy to understand for students?" and the lowest mean of students’ motivation for the question "Does the utilisation of this LMS improve students’ understanding?" is 1.40. From the result, it can be concluded that LMS in teaching and learning is an appropriate platform that should be increased at UTHM in accordance with worldwide technology advancements in education.